Model Lean Six Sigma di Industri Farmasi - Sari, Rini Mulyani; Nugraha, Evan (Winaya Mukti University, 2018)
Indonesia is one of the countries in the ASEAN Economic Community (AEC). To boost competitiveness and benefit from changes in the global industrial system at revolutionary era, lean six sigma approach to production systems in the pharmaceutical industry was used. The goal is to analyze the existing conditions, user expectations, how to overcome the obstacles that occur and the formulation of strengthening strategies on the production system of soft capsule lines. The method used an explanatory case study of production systems in the pharmaceutical industry using lean six sigma approach. The results of the research are the existing conditions of the production system have not met expectations, user expectations systems are not well understood, the formulation to overcome the constraints that occur in the production system and the formulation of the strengthening pharmaceutical industry’s production system strategy using lean six sigma approach.Indonesia termasuk salah negara dalam Masyarakat Ekonomi ASEAN (MEA). Dalam upaya mendongkrak daya saing dan memperoleh manfaat dari perubahan sistem industri global di era revolusi saat ini maka digunakan pendekatan lean six sigma pada sistem produksi di industri farmasi. Tujuan yang ingin dicapai adalah menganalisis kondisi eksisting, ekspektasi user, cara mengatasi kendala yang terjadi dan rumusan penguatan strategi pada`sistem produksi lini kapsul lunak. Metode yang digunakan adalah studi kasus eksplanatori sistem produksi di industri farmasi dengan menggunakan pendekatan lean six sigma. Hasil penelitian adalah kondisi eksisting sistem produksi belum memenuhi ekspektasi, sistem ekspektasi user belum dipahami dengan baik, rumusan cara mengatasi kendala yang terjadi pada sistem produksi, dan rumusan penguatan strategi sistem produksi industri farmasi dengan menggunakan pendekatan lean six sigma.